An electron density based analysis to establish the electronic adiabaticity of proton coupled electron transfer reactions. Issue 20 (5th June 2020) - Raucci, Umberto; Chiariello, Maria Gabriella; Coppola, Federico; Perrella, Fulvio; Savarese, Marika; Ciofini, Ilaria; Rega, Nadia
Abstract: Electrons and protons are the main actors in play in proton coupled electron transfer (PCET) reactions, which are fundamental in many biological (i.e., photosynthesis and enzymatic reactions) and electrochemical processes. The mechanism, energetics and kinetics of PCET reactions are strongly controlled by the coupling between the transferred electrons and protons. Concerted PCET reactions are classified according to the electronical adiabaticity degree of the process. To discriminate among different mechanisms, we propose a new analysis based on the use of electron density based indexes. We choose, as test case, the 3‐Methylphenoxyl/phenol system in two different conformations to show how the proposed analysis is a suitable tool to discriminate between the different degree of adiabaticity of PCET processes. The very low computational cost of this procedure is extremely promising to analyze and provide evidences of PCET mechanisms ruling the reactivity of many biological and catalytic systems. Abstract : Concerted Proton Coupled Electron Transfer (PCET) reactions are classified according to the electronical adiabaticity degree of the process. We propose a new analysis based on the use of electron density based indexes to discriminate between different PCET mechanisms. Our analysis opens a new scenario for ab‐initio simulations to investigate complex PCET mechanisms at very low computational cost.